La teledetección satelital y los sistemas de protección ambiental (2005)
The Teledetection offers great possibilities for the accomplishment of progresses in the knowledge of the nature, although everything has still not been obtained what of her it was expected because they think to make improvements in the level of space resolution, spectral and temporary of the data. In addition, a greater scientific rigor in the interpretation of the obtained results is necessary, treating about not drawing definitive conclusions of the made environmental studies by means of techniques of Teledetection. The models that are elaborated to process the data of Teledetection will have o have like objective to eliminate the effects caused by the variability in the conditions of pick up, the distortion caused by the atmosphere and the influence of parameters such as the position of the Sun, slope, exhibition, and altitude.